2017
DOI: 10.1088/1361-6641/aa7c25
|View full text |Cite
|
Sign up to set email alerts
|

Phase-change materials for non-volatile memory devices: from technological challenges to materials science issues

Abstract: Chalcogenide phase-change materials (PCMs), such as Ge-Sb-Te alloys, have shown outstanding properties, which has led to their successful use for a long time in optical memories (DVDs) and, recently, in non-volatile resistive memories. The latter, known as PCM memories or phase-change random access memories (PCRAMs), are the most promising candidates among emerging non-volatile memory (NVM) technologies to replace the current FLASH memories at CMOS technology nodes under 28 nm. Chalcogenide PCMs exhibit fast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
156
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 219 publications
(182 citation statements)
references
References 199 publications
4
156
1
5
Order By: Relevance
“…For example, Simpson et al, Takaura et al, Ohyanagi and Takaura, and Saito et al reported a series of GST‐SLs with 4 nm Sb 2 Te 3 sublayers, Tominaga et al reported some GST‐SLs with 1 nm Sb 2 Te 3 sublayer, Momand et al and Casarin et al reported some GST‐SLs with 3 nm Sb 2 Te 3 sublayers, Wang et al reported a GST‐SL with 6 nm Sb 2 Te 3 sublayers. Moreover, Kalikka et al and Noé et al fabricated a series of GST‐SLs with thickness‐varied Sb 2 Te 3 sublayers (varied from 1 to 8 nm). Also, Zhou et al reported a series of GST‐SLs with thickness‐varied Sb 2 Te 1 sublayers (varied from 1 to 4 nm).…”
Section: The Atomic Structure Of Gst‐slmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Simpson et al, Takaura et al, Ohyanagi and Takaura, and Saito et al reported a series of GST‐SLs with 4 nm Sb 2 Te 3 sublayers, Tominaga et al reported some GST‐SLs with 1 nm Sb 2 Te 3 sublayer, Momand et al and Casarin et al reported some GST‐SLs with 3 nm Sb 2 Te 3 sublayers, Wang et al reported a GST‐SL with 6 nm Sb 2 Te 3 sublayers. Moreover, Kalikka et al and Noé et al fabricated a series of GST‐SLs with thickness‐varied Sb 2 Te 3 sublayers (varied from 1 to 8 nm). Also, Zhou et al reported a series of GST‐SLs with thickness‐varied Sb 2 Te 1 sublayers (varied from 1 to 4 nm).…”
Section: The Atomic Structure Of Gst‐slmentioning
confidence: 99%
“…Moreover, the endurance of the N‐doped superlattice can reach 10 8 cycles, which is better than 10 6 cycles of GST‐SL (Figure o). Since many elements (such as C, N, O, Si, Ag, W, Bi, Sn) have been demonstrated to improve the performance of conventional bulk GST, similar attempts in GST‐SL should be expected.…”
Section: Optimization Of Superlattice For Advanced Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the power consumption, in particular the RESET current, is required for low power devices at CMOS technology nodes below 28 nm. Increasing the geometrical and thermal confinement of the phase‐change material in so‐called confined memory cells allows to improve the heating efficiency during the current pulses . Besides, many research efforts aim at optimizing the phase change material.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the geometrical and thermal confinement of the phase-change material in so-called confined memory cells allows to improve the heating efficiency during the current pulses. [4] Besides, many research efforts aim at optimizing the phase change material. Currently, a promising material engineering approach consists in introducing a chalcogenide superlattice (SL) in a memory cell, as first shown by Simpson et al [5] The SL is designed as a periodic stacking of nm-thick GeTe and van der Waals (vdW) Sb 2 Te 3 crystalline layers.…”
Section: Introductionmentioning
confidence: 99%